STUDY OF ANTIOXIDANT ACTIVITY COMBINATION OF ARABICA COFFEE LEAF ETHANOL EXTRACT AND ROSELLE FLOWER PETAL WATER EXTRACT - Yuni Retnaningtyas; Yodi Setiadi (UNEJ e-Proceeding)
Free radicals are molecules that have one or moreunpaired electrons. As we know that somecardiovascular diseases such as heart disease,diabetes mellitus, and cancer are diseases thattriggered by oxidative damage in the presence offree radicals. Excessive oxidation of the nucleicacids, proteins, fats and DNA cells can initiate theoccurrence of degenerative diseases such ascoronary heart disease, cataracts, cognitivedisorders and cancer (Leong and Shui, 2001; Pietta1999). Humans have had a defense system againstoxidants that come from within or from outside thebody in the form of diet. Defense of the body suchas enzymes peroxidase, catalase, glutathione,histidine, peptidin often still lacking due toenvironmental influences and poor diet (Pietta,1999).Antioxidants are molecules that can inhibit theoxidation of molecules that can produce freeradicals. Antioxidant is a compound that has theability to react with free radicals to produce a stablefree radical by accepting or donating electrons.Based on the source of, antioxidant divided into twokinds, namely natural antioxidants and antioxidantssynthetic (artificial). Synthetic antioxidants are mostoften used such as Propyl Error (PG), Butylatedhydroxyanisole (BHA), Butylated hydroxytoluene(BHT) and Tertbutylhydroquinone (TBHQ). Thesynthetic antioxidants can give side effects thatharmful to human health because it’s carcinogenic.Various studies on BHA and BHT indicate that thiscan cause tumors in laboratory animals at long-termuse (Kikuzaki, 1993). Natural antioxidant is anantioxidant that is obtained naturally in plants.Natural antioxidants are usually more desirable,because the level of better security and broaderbenefits in the food, health and cosmetics. Naturalantioxidants can be found in food of vegetables andfruits. As an example of natural antioxidants such asVitamin A, Vitamin C, Vitamin E, and Polyphenols.Their concerns about the potential side effects ofsynthetic antioxidants used as motivation for thestudy of natural antioxidants as one alternative.According to previous studies, plants with highphenol levels have high antioxidant activity as well,this is because most of the antioxidant compoundsare derivatives of phenol. Coffee is one agriculturalcommodity in Indonesia. In the Indonesian marketencountered two types of coffee, the Arabica coffee(Coffea arabica) and Robusta coffee (Coffeacanephora). Previous research showed that theleaves of the Arabica coffee (Coffea arabica)contains a lot of polyphenol compounds areefficacious as an antioxidant. Research conductedshows the results of a very high antioxidant activity(Pellegrini et al., 2003).Nowdays roselle (Hibiscus sabdariffa L.) become sopopular. Almost in every exhibition of medicinalplants, roselle is always introduced. This is due toalmost all parts of this plant can be used fortreatment, particularly for alternative medicine.Roselle contain chemical compounds that canprovide many benefits. According to the results ofprevious studies showing that the anthocyanincontent in the plant is effective in counteractingfree radicals cause cancer and other diseases(Mardiah et al., 2009).This research will be conducted to determine theantioxidant activity of ethanol extract of the leavesof the Arabica coffee (Coffea arabica) and waterextract of roselle calyx (Hibiscus sabdairffa) byDPPH (1,1-diphenyl-2-picrylhydrazyl) because themethod this is the simplest method, fast, easy,accurate, inexpensive, and capable of measuringthe various components that act as free radical orhydrogen donor. In addition DPPH method does notrequire a lot of reagents such as another method ofmeasuring antioxidant activity. Comparativecompounds used in measuring the activity of theseantioxidants are Vitamin C or ascorbic acid. Used asa comparison compound for the preparationVitamin C is widely used in the market and has beenshown to have antioxidant activity and relativelycheap. According to the study, Vitamin C is used bymany researchers as a benchmark test for theantioxidant activity